2015
DOI: 10.1080/15384101.2015.1026515
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Notch signaling and endocytosis by the Lgl neoplastic tumor suppressor

Abstract: The evolutionarily conserved neoplastic tumor suppressor protein, Lethal (2) giant larvae (Lgl), plays roles in cell polarity and tissue growth via regulation of the Hippo pathway. In our recent study, we showed that in the developing Drosophila eye epithelium, depletion of Lgl leads to increased ligand-dependent Notch signaling. lgl mutant tissue also exhibits an accumulation of early endosomes, recycling endosomes, early-multivesicular body markers and acidic vesicles. We showed that elevated Notch signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 94 publications
(123 reference statements)
8
40
1
Order By: Relevance
“…In Drosophila, Lgl controls endocytosis of the Notch regulator Sanpodo (Roegiers et al, 2005) in sensory precursor cells and attenuates Notch signaling. Also, in eye disc epithelia, Lgl associates with early to late endosomes and lysosomes and attenuates Notch signaling by limiting vesicle acidification (Parsons et al, 2014), which is achieved by promoting binding of vATPase to Vap33 (Portela et al, 2015). Likewise, Scrib optimizes BMP signaling by regulating the basolateral localization of the BMP receptor Thickveins and its internalization in Rab5-positive endosomes in wing epithelia (Gui et al, 2016).…”
Section: Male Gamete Development Requires Close Communication Betweenmentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila, Lgl controls endocytosis of the Notch regulator Sanpodo (Roegiers et al, 2005) in sensory precursor cells and attenuates Notch signaling. Also, in eye disc epithelia, Lgl associates with early to late endosomes and lysosomes and attenuates Notch signaling by limiting vesicle acidification (Parsons et al, 2014), which is achieved by promoting binding of vATPase to Vap33 (Portela et al, 2015). Likewise, Scrib optimizes BMP signaling by regulating the basolateral localization of the BMP receptor Thickveins and its internalization in Rab5-positive endosomes in wing epithelia (Gui et al, 2016).…”
Section: Male Gamete Development Requires Close Communication Betweenmentioning
confidence: 99%
“…Following vesicle endocytosis by CME, maturation of clathrin-coated pits initiates a cascade that locally converts PIP2 to different phosphatidylinositols and finally to PI(3)P, an essential feature of early endosomes, in a cascade that is important for vesicle uncoating (Marat and Haucke, 2016;Posor et al, 2015). Blocking early steps of CME by knocking down function of Shibire AP-2α, or Clathrin heavy chain may thus allow accumulation of higher levels of PIP2 in cyst cell plasma membranes, where it can promote EGFR activation.…”
Section: Male Gamete Development Requires Close Communication Betweenmentioning
confidence: 99%
“…lgl mutant tissue displayed accumulation of early endosomes, recycling endosomes, early-multivesicular body markers and acidic vesicles. Feeding vesicle de-acidifying drug Chloroquine could rescue the elevated Notch signaling in lgl mutant tissue [4,5]. This study links the Notch endocytosis with its role in tumorigenesis in vivo.…”
Section: Notch Signaling In Cell Proliferation and Cell Deathmentioning
confidence: 80%
“…Analysis of the 18 cell polarity–tissue growth interactors (Classes 3.1, 3.3, and 3.4) for their links to signaling pathways ( Figure 5 and Table S7 in File S1 ), revealed that many were associated with signaling pathways that Lgl, aPKC, or Crb have previously been shown to regulate in tissue growth control: the Hippo, Notch, and JNK pathways ( Grzeschik et al 2010a ; Parsons et al 2014a , b ; Portela et al 2015 ; Sun and Irvine 2011 ; Zhu et al 2010 ). Notably, other Lgl-interacting genes were associated with signaling pathways not previously linked to the negative regulation of tissue growth by Lgl: Wg, Decapentaplegic (Dpp), Hedgehog (Hh), Src, Ras, and lipid signaling/PI3K ( Figure 5 and Table S7 in File S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite detailed knowledge of the molecular interactions between the Crb, PAR, and Lgl complexes in the establishment and maintenance of cell polarity, how these mutually exclusive polarity modules interact to coordinate epithelial organization with tissue growth is less well understood. Thus, we have been investigating how these polarity regulators control tissue growth, and have discovered that Lgl’s, but not Scrib’s or Dlg’s, role in tissue growth control occurs via regulation of signaling pathways and that this function is independent of Lgl’s role in cell polarity ( Doggett et al 2011 , 2015 ; Grzeschik et al 2007 , 2010a ; Parsons et al 2014a ; Portela et al 2015 ; Richardson and Portela 2017 ). Of particular relevance here, our previous studies have shown that loss of lgl and the concomitant increase in aPKC activity, or increased levels of Crb, impair the Hippo tissue growth control pathway and are associated with ectopic cell proliferation, decreased apoptosis, and subsequent tissue overgrowth in the Drosophila eye ( Grzeschik et al 2010a , b ; Parsons et al 2010 , 2014a , b ; Portela et al 2015 ; Richardson and Portela 2017 ).…”
mentioning
confidence: 99%